COMPANY PAINTING A SYMBOL OF ART AND CULTURE - Pandey, Shikha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The relationship between knowledge and craft can guide a better understanding of social needs, and the researcher works to bridge this gap through informal sources such as arts and culture. Photographs of places and people experienced by tourists and foreign residents are often brought home as souvenirs and to disseminate information among people in society.